Development of Grazing Material for Married Couples who are Pregnant Out of Wedlock and Prevention Efforts in the Congregation of Christian Protestant Church in Indonesia - Maringan Sinambela (Budapest International Research and Critics University, 2022)
The purpose of this research is to find out how to develop grazing material for married couples who are pregnant out of wedlock and prevention efforts in Christian Protestant Church in Indonesia (Gereja Kristen Protestan Indonesia) congregations that are qualified, valid, practical and effective. Until this research was conducted, there were no standarized grazing materials for married couples who are pregnant out of wedlock and prevention efforts in the congregation of Christian Protestant Church in Indonesia. It was observed that there are still among pastors and church ministers reluctant and embarrassed to carry out grazing to married couples because they feel taboo to convey it. With the publication of this material, the pastor and minister of the church can convey this book of grazing material to the married couple to read and teach it to their children. This material is expected to be useful for teenagers, young people and also the elderly. The method used in this research is the Research and Development (R&D) method, which is the research method used to produce the product. The expert validators of this research were Pastors of Christian Protestant Church in Indonesia, in Tarutung and Sipoholon subdistrict, consisting of 10 people. From the results of the expert validators assessments on grazing materials for married couples who are pregnant out of wedlock and prevention efforts in the congregation, it is obtained that grazing materials developed in this research are suitable with a qualification level of eligibility criteria of 82.44%.